Lifestyle Analysis And Factors Affecting Consumer Interest In Post Pandemi Video On Demand Netflix Subscriptions - Aditya Rizki Rahmawati; Cecep Hermana (LPPM Universitas Buddhi Dharma, 2023)
The impact that has occurred since the presence of the Covid-19 pandemic has led to changes in people's lifestyles in carrying out their activities including carrying out their hobbies. On of the most popular activities for the public during the pandemic is watching online videos through streaming services using Video on Demand such as Netflix, which is known that Netflix is the online streaming application that is most in demand by the public as their choice of watching videos . Given this phenomenon, this study aims to analyze lifestyle and the factors that influence consumer interest in subscribing to Netflix after the pandemic. The type of research used in this study is a qualitative method by using literature/library research to obtain data and information used by researchers to analyze. The results of the study indicate that there are factors that influence consumer interest in subscribing to Netflix, namely, work, hobbies, age, gender, and individual attitude. The results of the analysis show that changes in lifestyle during the pandemic will greatly affect consumer interest in subscribing to Netflix.